2013
DOI: 10.1016/j.jcf.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in stable cystic fibrosis patients: Do we need higher antioxidant plasma levels?

Abstract: The majority of patients showed elevated plasma chromolipids that increased with age. Antioxidant vitamin reference ranges provide incomplete information on the redox status. CF patients with PI showed excessive oxidative stress damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
6
17
0
Order By: Relevance
“…5B). This agrees with the conventional paradigm in CF that ROS production by immune cells represents the major cause of airway injury, together with deficient anti-oxidant and anti-protease defences [31], [32].…”
Section: Resultssupporting
confidence: 90%
“…5B). This agrees with the conventional paradigm in CF that ROS production by immune cells represents the major cause of airway injury, together with deficient anti-oxidant and anti-protease defences [31], [32].…”
Section: Resultssupporting
confidence: 90%
“…Our previous study showed that AquADEKs attenuated selected OS markers in pediatric patients with CF [10]. Lezo et al also reported that CF patients showed elevated OS markers even in stable clinical conditions and with plasma antioxidants within the normal range [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Severe OS increases effects of pathological inflammation in patients with CF [7]. OS increases with age of patients, and its harmful effects can be ameliorated by properly mitigated antioxidant supplementation [8]. It has been suggested that antioxidant status of the patients should be monitored closely and antioxidant supplementation should be considered before significant deficiencies develop to ensure optimum antioxidant protection [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…This scenario might at least partly explain why (1) genetic polymorphisms in hepatic metabolizing enzymes are not major predisposing factors Alfirevic et al, 2003;Wolkenstein et al, 2005) and (2) sulfonamide reactions are detected in a higher number of subjects with AIDS and cystic fibrosis (van der Ven et al, 1994a;Lavergne et al, 2010) where oxidative stress plays an important role in the disease pathogenesis (van der Ven and Boers, 1997; Walmsley et al, 1997;Lezo et al, 2013). Nitroso SMX stimulates innate immunity through the activation of dendritic cells (Sanderson et al, 2007) and adaptive immunity through the generation of protein adducts.…”
Section: The Antigenicity and Immunogenicity Of Drugs That Acquirementioning
confidence: 99%